Surgical Precision in Lumbar Spinal Canal Stenosis: Optimizing Outcomes in a Young Adult with Suspected Infection through Decompression-Stabilization-Fusion - Putra, I Gusti Ngurah Paramartha Wijaya; Febyan; Ustriyana, Nyoman Gede Grenata Nanda (Indonesian Journal of Medicine, 2024)
Background: This case report examines the uncommon occurrence of Lumbar Spinal Canal Stenosis (LSCS) in a 23-year-old male patient, highlighting the diagnostic challenges and unique aspects of managing this condition in young adults. Typically associated with aging and degenerative changes, LSCS poses a diagnostic dilemma when encountered in a young individual with nonspecific causation. Case Presentation: The patient reported persistent lower back pain since February 2023, primarily on the right side, escalating over the past three months. The pain intensified during prolonged sitting, standing, and walking, alleviated by lying down and analgesics. Radiating pain to both buttocks and legs, particularly on the right side, accompanied a four-month history of persistent right foot numbness. Referred from RS Siloam Kupang to RSAD Denpasar and subsequently to RSUP Prof IGNG Ngoerah, the patient received a diagnosis of Lumbar Spinal Canal Stenosis at L2-L3-L4, L5-S1, with suspected Spondylitis TB. Results: This case underscores the intricacies of diagnosing Lumbar Spinal Canal Stenosis in young adults, emphasizing the exploration of non-traditional causes. The patient underwent Debridement-Decompression-Stabilization-Fusion-Biopsy+Culture, experiencing postoperative improvement. Cultures showed no growth, and biopsy results were nonspecific. The final diagnosis was Lumbar Spinal Canal Stenosis at L2-L3-L4, L5-S1 due to Spondylitis TB dd/Pyogenic Infection, with bilateral Neural Foraminal Stenosis Grade III at L5. The discussion focuses on the rarity of this presentation in young individuals, challenges in diagnosis, and the efficacy of decompression-stabilization-fusion treatment for achieving positive outcomes in young adult patients. Conclusion: The case discussion emphasizes the complexity of managing Lumbar Spinal Canal Stenosis in a young adult, particularly when infection is suspected. The decision to pursue Decompression-Stabilization-Fusion was rooted in the patient's age, the need for structural stability, and the suspicion of infection.